Emerging Digital Labor: Literature Review and Research Design - József, Pap; Csaba, Makó (Tér - Gazdaság - Ember/Journal of Region, Economy and Society, 2020)
The key players of the platform economy (e.g., Uber) represent the 21st century form of capitalism, which has the following key dimensions: 1) supported by patient capital, 2) network effects, 3) focal role of consumers. The paper outlines the major characteristics of changing labor, focusing on the platform work in a European context. This study employs a mixed approach: there is a literature review about platform economy and platform work, a methodological examination of the research objective, and the preliminary results of semi-structured interviews with workers in the platform economy. The results of the study clarify some key characteristics of digital labor, in particular platform work, and it lays out the research design of a European research project (https://crowd-work.eu/), which focuses on organizing digital workers in Europe.Keywords: platform economy, on-demand workforce, crowd work, future of work